2020
DOI: 10.3201/eid2609.200016
|View full text |Cite
|
Sign up to set email alerts
|

Risk-Based Estimate of Human Fungal Disease Burden, China

Abstract: F ungal diseases constitute a growing problem worldwide, causing a large, but poorly quantified, impact on public health (1). The incidence of fungal infections varies according to geographic region, socioeconomic conditions, and the number of persons with underlying conditions. China is one of the largest countries in the world (largest population and third largest land area). It has almost every type of weather niche, from the Pacific coast in the south to the snowy mountains in the Qinghai-Tibet Plateau, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 41 publications
(52 reference statements)
0
30
0
Order By: Relevance
“…Reports of TM disease are common in the AIDS population in the late stage. A meta-analysis [ 12 ] showed that the prevalence of TM among HIV patients in China ranged from 0.2% (95% CI: 0.1–0.5%) to 26.5% (95% CI: 16.2–43.5%). South China had the highest prevalence, estimated at 15.0% (95% CI: 11.0–20.4%), while Southwest China had the lowest prevalence, estimated at 0.3% [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports of TM disease are common in the AIDS population in the late stage. A meta-analysis [ 12 ] showed that the prevalence of TM among HIV patients in China ranged from 0.2% (95% CI: 0.1–0.5%) to 26.5% (95% CI: 16.2–43.5%). South China had the highest prevalence, estimated at 15.0% (95% CI: 11.0–20.4%), while Southwest China had the lowest prevalence, estimated at 0.3% [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…South China had the highest prevalence, estimated at 15.0% (95% CI: 11.0–20.4%), while Southwest China had the lowest prevalence, estimated at 0.3% [ 13 ]. It is estimated that there will be 4951 TM cases per year in patients with AIDS in southern China by 2050, and the endemic areas are increasing [ 12 ]. The disease is mostly localized to the lungs and skin and is related to exposure by inhalation or direct contact TM [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…South China had the highest prevalence, estimated at 15.0% (95% CI: 11.0-20.4%), while Southwest China had the lowest prevalence, estimated at 0.3% [13]. It is estimated that there will be 4,951 TM cases per year in patients with AIDS in southern China by 2050, and the endemic areas are increasing [12]. The disease is mostly con rmed in the lungs and skin and is related to TM contact by inhalation or direct contact [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Reports of TM disease are common in the AIDS population in the late stage. A meta-analysis [12] showed that the prevalence of TM among HIV patients in China ranged from 0.2% (95% CI: 0.1-0.5%) to 26.5% (95% CI: 16.2-43.5%). South China had the highest prevalence, estimated at 15.0% (95% CI: 11.0-20.4%), while Southwest China had the lowest prevalence, estimated at 0.3% [13].…”
Section: Introductionmentioning
confidence: 99%
“…Sporotrichosis is mainly found in central and South America: a new epidemic wave has spread from Rio de Janeiro to the North through cat transmission [23]. Only in China, talaromycosis is supposed to concern 20% HIVpositive subjects geographically exposed, resulting in 0.35 cases per 100,000 inhabitants, whereas its worldwide incidence is supposed to be close to 10,000 new cases per year [24]. Coccidioidomycosis due to Coccidioides immitis is largely underestimated: the actual incidence is likely closer to 140,000-150,000 cases per year, most occurring asymptomatically in America [1].…”
mentioning
confidence: 99%